The school assessment and quality assurance model in the European Schools - Garralón Barba, Javier (Avances en Supervisión Educativa, 2023)
The European Schools constitute an educational system of their own, 70 years old, which also has procedures for evaluating schools (whole school inspections) with characteristics that could be usefully applied to the Spanish educational system. These procedures have been extended, over time, to the "accredited European Schools", which are already twice as numerous as the traditional European Schools and which are inspected by means of an audit procedure that has many similarities –but also clear differences– with whole school inspections.
Keywords: evaluation; european schools; school inspection; audit; quality in education; quality assurance